IMPLEMENTASI PERBAIKAN KARAKTER DURIAN MELALUI TEKNOLOGI CROP IMPROVEMENT SAMBUNG DINI DI PONDOK PESANTREN BBE BARENG, JOMBANG - Susilo, Achmadi; Thohiron, Mochamad; Suryaningsih, Dwie Retna; Indarwati, Indarwati; Handoko, Candra Kristanto; Edison, Gabriel (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
This community service activity aims to improve the quality and productivity of durian farming in the Jombang area through the implementation of crop improvement technology, especially the early grafting method. In this activity, Pondok Pesantren Bhakti Bapak Emak (BBE) Bareng acts as an institution that educates students and local farmers about this technology. Through intensive training, field practice, and ongoing mentoring, participants are given knowledge and skills in choosing the right variety, carrying out the grafting process, and caring for durian plants effectively. Apart from that, close collaboration between educational institutions, local governments, research institutions and farming communities is also the key to the success of this program. By focusing on improving durian characteristics, it is hoped that this program can improve the quality and productivity of the fruit, as well as empower local farmers by increasing income and skills. As a result, it is anticipated that the program will have a broad positive impact on local communities and agriculture in the region